72=(a*10)+(a*2a)

Simple and best practice solution for 72=(a*10)+(a*2a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72=(a*10)+(a*2a) equation:


Simplifying
72 = (a * 10) + (a * 2a)

Reorder the terms for easier multiplication:
72 = (10a) + (a * 2a)

Reorder the terms for easier multiplication:
72 = (10a) + (2a * a)

Multiply a * a
72 = (10a) + (2a2)

Solving
72 = (10a) + (2a2)

Solving for variable 'a'.

Reorder the terms:
72 + (-10a) + (-2a2) = (10a) + (-10a) + (2a2) + (-2a2)

Combine like terms: (10a) + (-10a) = 0
72 + (-10a) + (-2a2) = 0 + (2a2) + (-2a2)
72 + (-10a) + (-2a2) = (2a2) + (-2a2)

Combine like terms: (2a2) + (-2a2) = 0
72 + (-10a) + (-2a2) = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(36 + (-5a) + (-1a2)) = 0

Factor a trinomial.
2((4 + -1a)(9 + a)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(4 + -1a)' equal to zero and attempt to solve: Simplifying 4 + -1a = 0 Solving 4 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1a = 0 + -4 -1a = 0 + -4 Combine like terms: 0 + -4 = -4 -1a = -4 Divide each side by '-1'. a = 4 Simplifying a = 4

Subproblem 2

Set the factor '(9 + a)' equal to zero and attempt to solve: Simplifying 9 + a = 0 Solving 9 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + a = 0 + -9 Combine like terms: 9 + -9 = 0 0 + a = 0 + -9 a = 0 + -9 Combine like terms: 0 + -9 = -9 a = -9 Simplifying a = -9

Solution

a = {4, -9}

See similar equations:

| 5(t-3)-3(2-t)= | | 15x-7x=8x | | 1.3+5(x-0.1)=-1.2-3x | | 2x+x^2+2x^2+x= | | (3x-45)= | | (2z)+(2z)+(3z-3)+(3z-3)=74 | | 2x+15-33=x | | 17+3x=125 | | (a-b+c)(-5)+61= | | 5m-20=0 | | 3(4q-1)-2(3q+4)= | | N+10=-10-6n-1 | | X=83-0.15x | | D=d-1-(3d+4)+(5-4d)-(7d+5)+5 | | 3(x-5)-8=-4(x-2) | | 10x+3=3-4x | | (a-b+c)(-5)-61a= | | 5x+4=4x-13 | | f(x)=2x^2+20x+58 | | 6(y-1)=x+4 | | 5x+3-2x+17=2 | | x+x+x+5x= | | -8p+1=2-9p | | y-12=2.5(x-3) | | x+4=6(y-1) | | A+7A-A= | | 25+15x=235 | | (5X-135)= | | X+0.15x=83 | | 3x+2(6-x)+5=37-9x | | 30+15x=235 | | -6-9b=3-6b |

Equations solver categories